Production of autoantibodies associated with polyclonal activation in Yersinia enterocolitica 0:8-infected mice - Ramos, Orivaldo Pereira [UNESP]; Cangiani Silva, Eloisa Elena [UNESP]; Falcão, Deise Pasetto [UNESP]; Machado de Medeiros, Beatriz Maria [UNESP] (Center Academic Publ Japan, 2005)
Polyclonal lymphocyte stimulation is one of the immunomodulatory mechanisms induced by arthritogenic pathogens. In this study we examined the polyclonal activation potential of a virulent strain of Y. enterocolitica serotype O:8 (WA 2707+) and its plasmidless isogenic pair (WA 2707-). SPF Swiss mice were infected intragastrically and spleen cells were obtained on days 7, 14, 21, 28, 35 and 42 after infection. The number of cells secreting nonspecific immunoglobulins of IgG, IgM and IgA isotypes was determined by the ELISPOT technique. The presence of serum-specific antibodies was investigated by ELISA and the presence of autoantibodies by dot-blot assay. Although the patterns of infection of the two bacterial strains were almost the same, only the animals infected with the virulent strain presented clinical anomalies. Neither arthritic nor inflammatory signs were observed in the joints of the infected animals. The greatest activation observed was that of the nonspecific IgM-secreting cells, and their peak of secretion occurred between the 28th and the 42nd day after infection, for both strains of Y. enterocolitica O:8. Only the animals infected with the virulent strain (WA 2707+) produced IgG-specific antibodies in the serum, from the 28th day after infection. The serum of animals infected with either strain showed reactivity to all the autologous constituents tested, mainly on the 28th and 42nd day after infection. It was concluded that infection of mice with either the virulent strain of Y. enterocolitica O:8 or with its plasmidless isogenic pair resulted in the polyclonal activation of the splenic B lymphocytes including some autoreactive clones.
Keywords: Autoantibodies; Polyclonal activation; Yersinia enterocolitica; Autoantibody; Immunoglobulin A antibody; Immunoglobulin G antibody; Immunoglobulin M antibody; Animal cell; Animal model; Antibody blood level; Antibody production; Antibody specificity; Arthritis; Bacterial growth; Bacterial strain; Bacterial virulence; Cell count; Colony forming unit; Controlled study; Dot hybridization; Enzyme linked immunosorbent assay; Enzyme linked immunospot assay; Female; Immunoglobulin production; Lymphocyte activation; Mouse; Nonhuman; Polyclonal activation; Spleen cell; Strain difference; Animals; Antibodies, Bacterial; Female; Immunoglobulins; Lymphocyte Count; Lymphocytes; Mice; Spleen; Time Factors; Yersinia Infections; Animalia; Bacteria (microorganisms)